Low-Temperature Strengths and Ductility of Various Tungsten Sheets - Yutaka Hiraoka; Hiroaki Kurishita (Advances in Materials Science and Engineering)
We used three kinds of tungsten sheets in this study. First, we examined microstructure such as grain size distribution using an optical microscope. Secondly, we carried out three-point bend tests at temperatures between about 290 and 500 K. Then, we examined fracture surface of a failed specimen using a scanning electron microscope. Lastly, by analyzing all these results, we evaluated apparent intergranular and transgranular fracture strengths and discussed strengths and ductility of tungsten. Additionally, we compared mechanical properties of tungsten with those of molybdenum.